DIPG-56. PRECLINICAL STUDIES OF DIANHYDROGALACTITOL (VAL-083) IN DIPG, AS SINGLE AGENT OR AS A COMBINATION WITH RADIATION OR AZD1775. Issue 2 (22nd June 2018) - Steino, Anne; Bacha, Jeffrey; Brown, Dennis; Mueller, Sabine
Abstract: Despite decades of trials, the prognosis for diffuse intrinsic pontine gliomas (DIPG) remains dismal. DIPG is inoperable and standard treatment is radiation alone, as the addition of chemotherapeutic agents, such as temozolomide, have not improved survival. In addition to inherent chemoresistance, treatment of DIPG is impeded by an intact blood-brain barrier (BBB). VAL-083 is a structurally unique bi-functional DNA-targeting agent that readily crosses the BBB. VAL-083 forms interstrand DNA crosslinks at N7-guanine, resulting in DNA double-strand breaks (DSB), S/G2-phase cell-cycle arrest, and ultimately cancer cell death. We have previously demonstrated that VAL-083 is able to overcome temozolomide-resistance in vitro and in vivo, and that its cytotoxicity is independent of the DNA-repair enzyme O6-methylguanine DNA-methyltransferase (MGMT). MGMT is almost universally expressed in DIPG and its expression is strongly correlated with temozolomide-resistance. VAL-083's distinct mechanism-of-action suggests the potential for combination with inhibitors of DNA DSB repair or S/G2 cell-cycle progression (e.g. Wee1 inhibitor AZD1775). Here, we investigated the effects of VAL-083 in combination with radiation, AZD1775 or irinotecan (topoisomerase inhibitor) in three DIPG cell-lines: SF10693 (H3.1), SF8628 (H3.3) and NEM157 (H3.3). VAL-083 showed activity at low uM-concentration in all three cell-lines. In addition, VAL-083 showed synergy with AZD1775 in all three cell-lines. Combined with its ability to cross the BBB, accumulate in brain tumor tissue and overcome MGMT-related chemoresistance, these results suggest VAL-083 as a potentially attractive treatment option for DIPG as single agent or in combination with AZD1775. Combination studies with radiation are ongoing and will be presented at the meeting.